Tingkat Kesulitan Keuangan dan Risiko Litigasi Terhadap Kinerja Perusahaan dengan Konservatisme Akuntansi Sebagai Variabel Mediasi - Dewi, Mira Triana; Bararoh, Tantri; Yuliarini, Sarah (E-Jurnal Akuntansi; Vol 32 No 8 (2022)DO - 10.24843/EJA.2022.v32.i08.p08, 2022)
This study aims to analyze the effect of financial distress and litigation risk on company performance through the mediating role of conservatism accounting in property and real estate companies on the Indonesia Stock Exchange in 2020. The results of the study explain that the level of financial difficulty and litigation risk has no significant effect on company performance, while conservatism has a significant negative effect. The results also explain that the level of financial distress has a significant negative effect on the accounting conservatism of the company, but the risk of litigation has no significant effect on the accounting conservatism of the company. The results also explain that accounting conservatism can perfectly mediate the effect of the level of financial distress on company performance, but cannot mediate the effect of litigation risk on company performance. Keywords: Financial Difficulty Level; Litigation Risk; Accounting Conservatism; Performance